A method for preparing structural chromogenic cellulose fabric

By using nano microspheres coated with sodium carboxymethylcellulose and polydopamine, the structure color paste is formed and cured at high temperature, the problem of easy destruction of structural color textiles is solved, and a structural color color cellulose fabric with high fastness and durability is achieved.

CN117107523BActive Publication Date: 2025-03-28CHANGSHU WEIYI TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310964859.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-08
Publication Date
2025-03-28
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

Existing structural colored textiles are easily damaged under external forces, resulting in structural color disappearance, limiting their use in textile applications.

Method used

Sodium carboxymethylcellulose is used as the binder to mix the polydopamine-coated nano microspheres with sodium carboxymethylcellulose, adjust the pH to 6.0-7.0, form a structural color paste, and cure at high temperature to improve the fastness of the structural color.

Benefits of technology

It significantly enhances the water-washing fastness and friction resistance of structural color textiles, ensuring the stability and durability of structural color.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117107523B_ABST
    Figure CN117107523B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a structural chromogenic cellulose fabric, comprising the following steps: preparing a sodium carboxymethyl cellulose aqueous solution with a mass concentration of 0.1% to 0.5%, mixing a nano-microsphere solution with the sodium carboxymethyl cellulose aqueous solution and adjusting the pH to 6.0 to 7.0, and stirring to obtain the structural color slurry; covering the surface of the cellulose fabric with the prepared structural color slurry, and placing it under a constant temperature and humidity environment for 1-6 hours to obtain the structural color cellulose fabric; the sodium carboxymethyl cellulose is used to connect the nano-microspheres and the cellulose fabric. The method for preparing the structural color cellulose fabric of the invention uses sodium carboxymethyl cellulose as a binder to bond the nanoparticles; and adjusting the pH to an acidic range of 6.0 to 7.0, so that the structural color slurry undergoes an esterification reaction under a partial acidic condition and at 120°C to 150°C, so that the carboxyl group of the sodium carboxymethyl cellulose itself is esterified and cross-linked with the hydroxyl group of the cellulose fabric, thereby improving the washing fastness of the structural color.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application date of July 8, 2022, application number 2022108153067, and invention name “A structural chromogenic cellulose fabric and its preparation method”. Technical Field

[0002] The invention relates to the technical field of structural color textiles, and in particular to a method for preparing a structural color-forming cellulose fabric with improved structural color fastness based on sodium carboxymethyl cellulose. Background Art

[0003] Structural color has nothing to do with pigmentation, but is an optical effect caused by the submicroscopic structure of organisms. Due to the advantages of structural color, such as non-fading, environmental protection and iridescence effect, it has broad application prospects in the fields of display, decoration, anti-counterfeiting, etc. At present, the research on artificial preparation of structural color fabrics is mainly achieved through the method of photonic crystals. The color of photonic crystal structural color prepared by self-assembly on the surface of white fabrics is often pale and low in contrast, which is the result of the influence of a large amount of reflected background light on the fabric surface and the incoherent scattered light in the photonic crystals.

[0004] In order to solve this problem, enhance the contrast of structural colors, and obtain bright and vivid structural colors, patent CN105182567 pre-dye the fabric and then deposit photonic crystals, and patent CN111648144 introduces carbon black into photonic crystals to obtain bright structural colors. However, since the nanoparticles and the nanoparticles and the substrate are mainly bound by weak forces such as hydrogen bonds and van der Waals forces, the array is easily destroyed under external forces (washing, friction, bending), resulting in the disappearance of structural colors, which greatly limits the application of structural colors in textiles.

[0005] Polydopamine (PDA) is the main substance of natural melanin. PDA exhibits many of the remarkable optical, electrical, and magnetic properties of natural melanin, as well as excellent biocompatibility. It also has strong adhesion similar to mussel adhesion protein, and can adhere to the surface of almost all substrates, regardless of the physical and chemical properties of the substrate surface. Therefore, the use of PDA in structural color materials can not only enhance color visibility but also improve its structural stability to meet the wearability of textiles. However, although the use of polydopamine-doped / coated samples or polydopamine-coated core-shell nanoparticles can increase the adhesion between particles, because polydopamine itself is black, the amount used is limited, and the improvement in structural stability is limited, which still cannot meet the practical application needs of textiles.

[0006] Gu et al. from Southeast University (Nanoscale, 2018, 10: 3673-3679.) modified silica (SiO2) microspheres with PDA to prepare SiO2@PDA nanospheres with a core-shell structure, and further prepared SiO2@PDA amorphous photonic arrays by spraying. Then, by treating them with ammonia vapor, the PDA on the surface of the microspheres reacted with ammonium ions to form new covalent bonds, thereby increasing the interaction force between structural elements. However, covalent crosslinking only exists at point contacts with the nanospheres, so the improvement in fastness is limited.

[0007] Sodium carboxymethyl cellulose is a water-soluble cellulose ether obtained by chemical modification of natural cellulose. It is the main ionic cellulose gum. Sodium carboxymethyl cellulose can form a film on the surface of the material, which can play a certain protective role on the material. Sodium carboxymethyl cellulose generally appears as white fibers or some granular powders. It has the characteristics of no taste, no odor, good hygroscopicity, and insoluble in organic solvents. It is generally used as a thickener in food, as a binder and anti-reprecipitation agent in the daily chemical industry, and as a sizing agent and protective colloid of printing paste in the printing and dyeing industry. In order to improve the color fastness of the structure, sodium carboxymethyl cellulose can be used as a binder to bond the nanoparticles. However, sodium carboxymethyl cellulose is a water-soluble polymer, and its wash fastness problem needs to be solved.

[0008] Therefore, developing a preparation method for structural chromophores with excellent optical properties and high structural stability is of great significance for promoting the practical application of structural chromophore technology in the coloring of products such as textiles.

[0009] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0010] In view of this, in order to overcome the defects of the prior art, the present invention provides a method for preparing a structural chromogenic cellulose fabric, which is a method for improving the structural color fastness of the fabric based on sodium carboxymethyl cellulose as an adhesive.

[0011] In order to achieve the above object, the present invention adopts the following technical solutions:

[0012] A method for preparing a structural chromogenic cellulose fabric comprises the following steps:

[0013] Dispersing the polydopamine-coated nanospheres in water to obtain a nanosphere solution with a mass concentration of 20-50 wt %;

[0014] A sodium carboxymethyl cellulose aqueous solution with a mass concentration of 0.1% to 0.5% is prepared, the nano-microsphere solution and the sodium carboxymethyl cellulose aqueous solution are mixed and the pH is adjusted to 6.0 to 7.0, and the structural color slurry is obtained after being stirred evenly;

[0015] The prepared structural color slurry is applied to the surface of the cellulose fabric with a thickness of 0.1-0.5 mm; the fabric is placed in a constant temperature and humidity environment for 1-6 hours to obtain the structural color cellulose fabric; the structural color cellulose fabric is then placed at 120-150° C. for 30-120 minutes for curing to obtain a structural color cellulose fabric with good durability after curing. The preferred fabric type is cellulose fabric, which not only has a high hydroxyl content but also can withstand a certain temperature.

[0016] According to some preferred embodiments of the present invention, the polydopamine-coated nanoparticles are prepared by the following method: dopamine hydrochloride and an iron salt oxidation catalyst are added to an aqueous dispersion of the nanoparticles, the mixture is evenly mixed, the temperature is raised to 30-60° C., and the reaction is stirred for 5-120 minutes to obtain polydopamine-coated nanoparticles.

[0017] According to some preferred embodiments of the present invention, the nanospheres are polystyrene-divinylbenzene polymer microspheres (PS-DVB microspheres).

[0018] Directly using sodium carboxymethylcellulose to adhere polystyrene-divinylbenzene polymer microspheres to cotton fabric will cause optical effects on the one hand, and on the other hand, PS-DVB microspheres are hydrophobic beads, and the binding force with sodium carboxymethylcellulose is not strong enough. Therefore, the present invention also uses polydopamine-coated nano-microspheres to simultaneously improve the refractive index of polystyrene-divinylbenzene polymer microspheres. The amino group on polydopamine reacts with the carboxyl group of sodium carboxymethylcellulose to form an amide bond, which improves the binding force of the nano-microspheres and sodium carboxymethylcellulose, and further improves the fastness to washing and the friction resistance. At the same time, by adjusting the particle size of the polystyrene-divinylbenzene polymer microspheres (PS-DVB microspheres), the regulation of the structural color hue presented thereto can be achieved, and as the particle size gradually increases, the prepared structural color-producing product gradually undergoes red shift.

[0019] According to some preferred embodiments of the present invention, the volume ratio of styrene to divinylbenzene during polymerization in the polystyrene-divinylbenzene polymer microspheres is 9:1-8:2.

[0020] According to some preferred embodiments of the present invention, the aqueous dispersion of nanospheres is prepared by the following method: dispersing polystyrene-divinylbenzene polymer microspheres in water and treating them under ultrasound for 5-30 minutes to obtain an aqueous dispersion of nanospheres with a concentration of 1-10 mg / mL.

[0021] According to some preferred embodiments of the present invention, the average particle size of the nano-microspheres is 180-350 nm; and the monodispersity index of the nano-microspheres is less than 0.1.

[0022] According to some preferred embodiments of the present invention, the polydopamine-coated nanospheres are prepared by adding dopamine hydrochloride to a concentration of 0.1-1 mg / mL; adding the iron salt oxidation catalyst to a concentration of 0.1-1 mg / mL. Polydopamine (PDA) is the main substance of natural melanin. Although core-shell nanoparticles coated with polydopamine can increase the adhesion between particles, the amount of polydopamine used is limited because it has a black color. The improvement of structural stability is limited, and it is still difficult to meet the practical application needs of textiles.

[0023] According to some preferred embodiments of the present invention, when preparing the polydopamine-coated nanoparticles, the product obtained by the reaction is washed with deionized water, dispersed under ultrasound and then collected by centrifugation to obtain the polydopamine-coated nanoparticles.

[0024] According to some preferred implementation aspects of the present invention, the volume ratio of the nanosphere solution to the sodium carboxymethyl cellulose aqueous solution in the structural color paste is 2:1 to 1:2.

[0025] According to some preferred embodiments of the present invention, the substance used to adjust the pH is preferably hydrochloric acid.

[0026] According to some preferred embodiments of the present invention, the iron salt oxidation catalyst is one or more selected from ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate.

[0027] According to some preferred implementation aspects of the present invention, the constant temperature and humidity environment has a temperature of 30-60° C. and a humidity of 50-70%.

[0028] The present invention also provides a method for preparing the structural chromogenic cellulose fabric to prepare the structural chromogenic cellulose fabric.

[0029] Compared with the prior art, the invention is beneficial in that: the preparation method of the structural color cellulose fabric of the invention comprises the following steps: the nano-microsphere solution is mixed with a sodium carboxymethyl cellulose aqueous solution to obtain a structural color slurry, and the sodium carboxymethyl cellulose is used as a binder to bond the nano-particles, thereby improving the fastness of the structural color; and the pH is adjusted to an acidic range of 6.0 to 7.0, so that the structural color slurry undergoes an esterification reaction under a slant-acidic condition and at 120° C. to 150° C., so that the carboxyl group and the hydroxyl group of the sodium carboxymethyl cellulose itself are esterified and cross-linked, and the carboxyl group and the hydroxyl group on the cotton fabric are also cross-linked, and finally a cross-linked esterification product is formed, so that the sodium carboxymethyl cellulose is prompted to form a physical and chemical cross-link between the nano-microsphere elements and between the contact surface of the sodium carboxymethyl cellulose and the cotton fabric substrate, thereby significantly enhancing the water washing fastness and friction resistance of the structural color cotton fabric, etc.; at the same time, the nano-microspheres coated on polydopamine are used, so that the amino groups on the polydopamine react with the carboxyl groups of the sodium carboxymethyl cellulose to form amide bonds, thereby improving the binding force between the nano-microspheres and the sodium carboxymethyl cellulose, and further improving the water washing fastness and friction resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 is a scanning electron microscope image of the surface of the structural chromogenic cellulose fabric prepared in Example 1 of the present invention;

[0032] Figure 2 This is a microscope photograph of the structural chromogenic cellulose fabric prepared in Example 1 of the present invention after 50 bending and folding tests. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] The basic principle of the present invention is as follows: it is difficult for structural color beads to be directly firmly attached to a substrate such as cotton fabric, so the fastness of general structural colors is low and it is difficult to withstand washing and friction. Sodium carboxymethyl cellulose is a water-soluble cellulose ether obtained by chemically modifying natural cellulose and is the main ionic cellulose glue. In order to improve the fastness of structural colors in the present invention, sodium carboxymethyl cellulose is used as a binder to bond the nanoparticles.

[0035] However, sodium carboxymethyl cellulose is a water-soluble polymer, and its washing fastness needs to be solved at the same time. In order to improve the washing fastness, the present invention adjusts the structural color slurry to a partial acidity of 6 to 7, and adds a high-temperature color fixing process when preparing the fabric. Under the condition of controlling the partial acidity, sodium carboxymethyl cellulose is heated at 120°C-150°C for a period of time, and an esterification reaction occurs, so that the carboxyl group and hydroxyl group of sodium carboxymethyl cellulose itself are esterified and cross-linked, and the carboxyl group and the hydroxyl group on the cotton fabric are also cross-linked, and finally a cross-linked esterification product is formed, which promotes the physical and chemical cross-linking of sodium carboxymethyl cellulose between the nano-microsphere elements and the contact surface between sodium carboxymethyl cellulose and the cotton fabric substrate, and significantly enhances the washing fastness and friction resistance of the structural color product.

[0036] In addition, directly using sodium carboxymethylcellulose to adhere polystyrene-divinylbenzene polymer microspheres to cotton fabric will cause optical effects on the one hand, and on the other hand PS-DVB microspheres are hydrophobic beads, and the binding force with sodium carboxymethylcellulose is not strong enough. Therefore, the present invention also uses polydopamine to coat nano microspheres to improve the refractive index of polystyrene-divinylbenzene polymer microspheres. The amino group on the polydopamine reacts with the carboxyl group of sodium carboxymethylcellulose to form an amide bond, which improves the binding force of the nano microspheres and sodium carboxymethylcellulose, and further improves the fastness to washing and the friction resistance. At the same time, by adjusting the particle size of the cross-linked polystyrene-polydivinylbenzene nano microspheres, the regulation of the structural color hue presented can be achieved, and as the particle size gradually increases, the structural color-producing product prepared gradually shifts red.

[0037] Based on the above principle, the preparation method of improving the color fastness of cotton fabric structure based on sodium carboxymethyl cellulose of the present invention specifically comprises the following steps:

[0038] (1) Dispersion of nanospheres

[0039] A 1-10 mg / mL aqueous dispersion of polystyrene-divinylbenzene polymer microspheres is prepared and ultrasonically treated for 5-30 minutes to fully disperse the microspheres. The volume ratio of styrene to divinylbenzene during polymerization is 9:1-8:2, the average particle size of the nano-microspheres is 180-350 nm, the sphericity is good, and the monodispersity index of the microspheres is less than 0.1, so as to adjust the structural color hue.

[0040] (2) Surface coating of nanospheres

[0041] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.1-1 mg / mL, add iron salt oxidation catalyst to make its concentration 0.1-1 mg / mL, then increase the temperature to 30-60°C, stir and react for 5-120 minutes to promote dopamine oxidation polymerization and wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse it with ultrasonic wave, and collect it by centrifugation to obtain polydopamine-coated nano-microspheres.

[0042] The iron salt oxidation catalyst is one or more selected from ferric chloride, ferric sulfate, ferric nitrate and ferric acetate.

[0043] (3) Configuration of structural color paste

[0044] The polydopamine-coated nanospheres prepared in step (2) are dispersed in deionized water at a mass concentration of 20-50 wt %, and dispersed by ultrasonication for 5-30 min to obtain a nanosphere solution.

[0045] A sodium carboxymethyl cellulose aqueous solution is prepared with a mass concentration of 0.1% to 0.5%.

[0046] The nano-microsphere solution is mixed with the sodium carboxymethyl cellulose aqueous solution, hydrochloric acid is added to adjust the pH to 6.0-7.0, and the mixture is stirred evenly to obtain a structural color slurry.

[0047] The volume ratio of the nano-microsphere solution to the sodium carboxymethyl cellulose aqueous solution in the structural color paste is 2:1 to 1:2.

[0048] (4) Preparation of structural color cotton fabrics

[0049] The structural color slurry prepared in step (3) is uniformly cast onto the surface of the cotton fabric with a thickness of 0.1-0.5 mm, and then assembled in a constant temperature and humidity environment for 1-6 hours to obtain a structural color-forming cellulose fabric.

[0050] The assembly conditions in a constant temperature and humidity environment are a temperature of 30-60°C and a humidity of 50-70%.

[0051] (5) Curing of structural color cotton fabrics

[0052] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 120-150° C. for 30-120 minutes to obtain a structural chromogenic cellulose fabric with good durability.

[0053] Example 1

[0054] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0055] (1) Dispersion of nanospheres

[0056] Polystyrene-divinylbenzene polymer microspheres with a particle size of 215 nm, a monodispersity index of 0.06, and a crosslinking ratio of 8:2 were selected, and a 5 mg / mL aqueous dispersion was prepared and ultrasonicated for 15 min to fully disperse.

[0057] (2) Surface coating of nanospheres

[0058] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.3 mg / mL, add ferric chloride oxidation catalyst to make its concentration 0.3 mg / mL, then raise the temperature to 40°C, stir and react for 60 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse it by ultrasonic wave, and collect it by centrifugation to obtain polydopa-coated nano-microspheres.

[0059] (3) Configuration of structural color paste

[0060] The surface-coated nano-microspheres obtained in step (2) are dispersed in deionized water at a mass concentration of 35 wt %, and dispersed by ultrasonication for 20 min to obtain a nano-microsphere solution.

[0061] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.4%.

[0062] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed in a volume ratio of 2:1, hydrochloric acid was added to adjust the pH to 6.5, and the mixture was stirred evenly to obtain a structural color slurry.

[0063] (4) Preparation of structural color cotton fabrics

[0064] The structural color slurry prepared in step (3) was uniformly cast onto the surface of the cotton fabric with a thickness of 0.4 mm, and then assembled in an environment of 30° C. and 50% humidity for 4 hours to obtain a structural color-producing cellulose fabric.

[0065] (5) Self-esterification curing of structural color cotton fabrics

[0066] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 140° C. for 60 minutes to obtain a durable green structural chromogenic cellulose fabric.

[0067] Example 2

[0068] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0069] (1) Dispersion of nanospheres

[0070] Polystyrene-divinylbenzene polymer microspheres with a particle size of 181 nm, a monodispersity index of 0.04, and a crosslinking ratio of 8.5:1.5 were selected, and a 6 mg / mL aqueous dispersion was prepared and ultrasonicated for 20 minutes to fully disperse.

[0071] (2) Surface coating of nanospheres

[0072] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.4 mg / mL, add iron sulfate oxidation catalyst to make its concentration 0.4 mg / mL, then raise the temperature to 45°C, stir and react for 50 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse by ultrasonic wave, and collect by centrifugation to obtain polydopamine-coated nano-microspheres.

[0073] (3) Configuration of structural color paste

[0074] The surface-coated nanospheres obtained in step (2) are dispersed in deionized water at a mass concentration of 30 wt %, and dispersed by ultrasonication for 20 min to obtain a nanosphere solution.

[0075] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.5%.

[0076] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed at a volume ratio of 1.5:1, hydrochloric acid was added to adjust the pH to 6.4, and the mixture was stirred evenly to obtain a structural color slurry.

[0077] (4) Preparation of structural color cotton fabrics

[0078] The structural color slurry prepared in step (3) was uniformly cast onto the surface of the cotton fabric with a thickness of 0.4 mm, and then assembled in an environment of 30° C. and 70% humidity for 5 hours to obtain a structural color-producing cellulose fabric.

[0079] (5) Self-esterification curing of structural color cotton fabrics

[0080] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 145° C. for 40 minutes to obtain a blue structural chromogenic cellulose fabric with good durability.

[0081] Example 3

[0082] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0083] (1) Dispersion of nanospheres

[0084] Polystyrene-divinylbenzene polymer microspheres with a particle size of 243 nm, a monodispersity index of 0.03, and a crosslinking ratio of 9:1 were prepared with a 2 mg / mL aqueous dispersion of polystyrene-divinylbenzene polymer microspheres and subjected to ultrasonic treatment for 15 min to fully disperse the microspheres.

[0085] (2) Surface coating of nanospheres

[0086] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.5 mg / mL, add ferric nitrate oxidation catalyst to make its concentration 0.4 mg / mL, then raise the temperature to 35°C, stir and react for 70 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse by ultrasonic wave, and collect by centrifugation to obtain polydopamine-coated nano-microspheres.

[0087] (3) Configuration of structural color paste

[0088] The surface-coated nano-microspheres obtained in step (2) are dispersed in deionized water at a mass concentration of 45 wt %, and dispersed by ultrasonication for 25 min to obtain a nano-microsphere solution.

[0089] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.2%.

[0090] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed in a volume ratio of 1:2, hydrochloric acid was added to adjust the pH to 6.2, and the mixture was stirred evenly to obtain a structural color slurry.

[0091] (4) Preparation of structural color cotton fabrics

[0092] The structural color slurry prepared in step (3) is uniformly cast onto the surface of the cotton fabric with a thickness of 0.3 mm, and then assembled in an environment of temperature 25° C. and humidity 60% for 6 hours to obtain a structural color-producing cellulose fabric.

[0093] (5) Self-esterification curing of structural color cotton fabrics

[0094] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 130° C. for 100 minutes to obtain a red structural chromogenic cellulose fabric with good durability.

[0095] Example 4

[0096] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0097] (1) Dispersion of nanospheres

[0098] Polystyrene-polydivinylbenzene cross-linked (PS-DVB) nanospheres with a particle size of 215 nm, a monodispersity index of 0.06, and a cross-linking ratio of 8:2 were selected, a 4 mg / mL aqueous dispersion was prepared, and ultrasonic treatment was performed for 15 minutes to fully disperse them.

[0099] (2) Surface coating of nanospheres

[0100] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.6 mg / mL, add iron acetate oxidation catalyst to make its concentration 0.6 mg / mL, then raise the temperature to 50°C, stir and react for 15 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse by ultrasonic wave, and collect by centrifugation to obtain polydopamine-coated nano-microspheres.

[0101] (3) Configuration of structural color paste

[0102] The surface-coated nano-microspheres obtained in step (2) are dispersed in deionized water at a mass concentration of 35 wt %, and dispersed by ultrasonication for 20 min to obtain a nano-microsphere solution.

[0103] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.4%.

[0104] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed in a volume ratio of 1:1, hydrochloric acid was added to adjust the pH to 6.7, and the mixture was stirred evenly to obtain a structural color slurry.

[0105] (4) Preparation of structural color cotton fabrics

[0106] The structural color slurry prepared in step (3) is uniformly cast onto the surface of the cotton fabric with a thickness of 0.3 mm, and then assembled in an environment of a temperature of 50° C. and a humidity of 70% for 2 hours to obtain a structural color-producing cellulose fabric.

[0107] (5) Self-esterification curing of structural color cotton fabrics

[0108] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 120° C. for 120 minutes to obtain a durable green structural chromogenic cellulose fabric.

[0109] Example 5

[0110] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0111] (1) Dispersion of nanospheres

[0112] Polystyrene-divinylbenzene polymer microspheres with a particle size of 181 nm, a monodispersity index of 0.04, and a crosslinking ratio of 8.5:1.5 were selected, and a 7 mg / mL aqueous dispersion was prepared and fully dispersed by ultrasonic treatment for 25 minutes.

[0113] (2) Surface coating of nanospheres

[0114] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.6 mg / mL, add ferric chloride oxidation catalyst to make its concentration 0.6 mg / mL, then raise the temperature to 50°C, stir and react for 15 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse it by ultrasonic wave, and collect it by centrifugation to obtain polydopamine-coated nano-microspheres.

[0115] (3) Configuration of structural color paste

[0116] The surface-coated nanospheres obtained in step (2) were dispersed in deionized water at a mass concentration of 30 wt %, and dispersed by ultrasonication for 16 min to obtain a nanosphere solution.

[0117] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.2%.

[0118] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed in a volume ratio of 1:1, hydrochloric acid was added to adjust the pH to 6.5, and the mixture was stirred evenly to obtain a structural color slurry.

[0119] (4) Preparation of structural color cotton fabrics

[0120] The structural color slurry prepared in step (3) was uniformly cast onto the surface of the cotton fabric with a thickness of 0.3 mm, and then assembled in an environment of a temperature of 30° C. and a humidity of 60% for 4 hours to obtain a structural color-producing cellulose fabric.

[0121] (5) Self-esterification curing of structural color cotton fabrics

[0122] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 135° C. for 90 minutes to obtain a durable blue structural chromogenic cellulose fabric.

[0123] Example 6

[0124] The preparation method of the structural color cotton fabric in this embodiment comprises the following steps:

[0125] (1) Dispersion of nanospheres

[0126] Polystyrene-divinylbenzene polymer microspheres with a particle size of 243 nm, a monodispersity index of 0.03, and a crosslinking ratio of 9:1 were selected, and a 5 mg / mL aqueous dispersion was prepared and ultrasonicated for 20 minutes to fully disperse.

[0127] (2) Surface coating of nanospheres

[0128] Add dopamine hydrochloride to the polystyrene-divinylbenzene polymer microsphere aqueous dispersion prepared in step (1) to make its concentration 0.4 mg / mL, add iron sulfate oxidation catalyst to make its concentration 0.5 mg / mL, then raise the temperature to 40°C, stir and react for 20 minutes to promote dopamine oxidation polymerization to wrap nano-microspheres. After the reaction, wash the product with deionized water, disperse by ultrasonic wave, and collect by centrifugation to obtain polydopamine-coated nano-microspheres.

[0129] (3) Configuration of structural color paste

[0130] The surface-coated nano-microspheres obtained in step (2) were dispersed in deionized water at a mass concentration of 25 wt %, and dispersed by ultrasonication for 16 min to obtain a nano-microsphere solution.

[0131] A sodium carboxymethyl cellulose aqueous solution was prepared with a mass concentration of 0.3%.

[0132] The nanosphere solution and the sodium carboxymethyl cellulose aqueous solution were mixed in a volume ratio of 1:1, hydrochloric acid was added to adjust the pH to 6.5, and the mixture was stirred evenly to obtain a structural color slurry.

[0133] (4) Preparation of structural color cotton fabrics

[0134] The structural color slurry prepared in step (3) was uniformly cast onto the surface of the cotton fabric with a thickness of 0.4 mm, and then assembled in an environment of 30° C. and 50% humidity for 6 hours to obtain a structural color-producing cellulose fabric.

[0135] (5) Self-esterification curing of structural color cotton fabrics

[0136] The structural chromogenic cellulose fabric obtained in step (4) is placed in a drying room and treated at 130° C. for 110 minutes to obtain a blue structural chromogenic cellulose fabric with good durability.

[0137] Comparative Example 1

[0138] The difference between this comparative example and Example 1 is that step 5 in Example 1 is omitted in this comparative example, that is, this comparative example does not include the step of high-temperature curing of the structural chromogenic cellulose fabric.

[0139] Comparative Example 2

[0140] The difference between this comparative example and Example 1 is that the nano-microspheres in the structural color paste in this comparative example directly use unmodified polystyrene-divinylbenzene polymer microspheres instead of the polydopamine-coated nano-microspheres in the example.

[0141] Comparative Example 3

[0142] The difference between this comparative example and Example 1 is that in this comparative example, the high temperature curing condition in step 5 of Example 1 is reduced, that is, the curing condition adopted in this comparative example is curing treatment at 100° C. for 30 minutes.

[0143] Results and Tests

[0144] 1) SEM image of the surface of structural chromogenic cellulose fabric

[0145] Figure 1 This is a scanning electron microscope image of the surface of the structural chromogenic cellulose fabric prepared in Example 1.

[0146] from Figure 1 It can be seen that the nanospheres are encapsulated on the surface of textiles by sodium carboxymethyl cellulose, and the nanoparticles have a long-range disordered and short-range ordered arrangement structure.

[0147] 2) Bending and folding test of structural chromogenic cellulose fabric

[0148] Figure 2 This is the result of 50 bending and folding tests on the structural chromogenic cellulose fabric prepared in Example 1.

[0149] The bending and folding test is to fold and bend one end of the obtained textile from the horizontal direction until it touches the other end, and use an optical microscope to observe the change of the structural color of the surface of the structural color textile after folding and bending. It can be seen from the figure that the prepared structural color cellulose fabric has a stable structure and good anti-folding effect.

[0150] 3) Soap-resistant color fastness and bending and folding test

[0151] Table 1 shows the test results of color fastness to soap washing and bending and folding of the structural color cellulose fabrics prepared in Examples 1 to 6. The color fastness to soap washing is measured according to GB / T3921-2008 "Textiles - Tests for Color Fastness - Color Fastness to Soap Washing"; the bending and folding test is to fold and bend one end of the obtained textile from the horizontal direction until it touches the other end, and use a scanning electron microscope and a digital camera to observe the changes in the surface structural color and amorphous photon array of the structural color textile before and after folding and bending.

[0152] Table 1 Washing fastness and bending and folding test results of the structural chromogenic cellulose fabric in the embodiment

[0153]

[0154] The fading values ​​in Table 1 represent the washing fastness, which is scored on a scale of 1-5, with 1 being the lowest and 5 being the highest. It can be seen from the data in Table 1 that the structural chromogenic cellulose fabric prepared in the embodiment has excellent color fastness and a stable structure. However, the result of not curing in Comparative Example 1 caused severe fading, and many polyvinyl divinyl benzene particles were washed out in the soaping liquid. At the same time, the curing temperature in Comparative Example 3 was low, and the washing fastness was low.

[0155] The nano-microspheres of PS-DVB are originally colorless, and they develop color after forming a certain nano-stacked structure. However, the particles are very easy to fall off, so a stronger curing effect is required. The present invention discloses a method for improving the color fastness of cotton fabric structure based on sodium carboxymethyl cellulose, and the key lies in using the fixing effect of sodium carboxymethyl cellulose, and sodium carboxymethyl cellulose can adhere firmly to cellulose. The technical scheme of the present invention is: a sodium carboxymethyl cellulose solution with a certain solid content and a dispersion of high-refractive-index core-shell nano-microspheres coated with dopamine are mixed evenly in a certain volume ratio and then arranged on cotton fabric, and then the cotton fabric is placed in a drying device for drying and curing. After the liquid is completely volatilized, a soft, bright, and color fastness-excellent structural color-forming cellulose fabric can be obtained, so that the bonding strength between the structural elements and between the structural elements and the substrate is improved, the structure is stable, and the color durability is improved. The method of the present invention is simple to operate, low in cost, mild in reaction conditions, does not involve any organic solvents and polymer functional monomers, and dopamine and sodium carboxymethyl cellulose are both natural products, which are ecological and environmentally friendly. The method effectively solves the defects of the prior art that the structural color is easy to fall off and unstable, can ensure the durability of the structural color of cotton fabrics, and has the advantages of easy implementation, low cost, green environmental protection and good universality.

[0156] The equipment and raw materials used in the above-mentioned embodiments can be purchased from the market or are commonly used in this field. The methods in the above-mentioned embodiments, if not otherwise specified, are conventional methods in this field. The raw materials not specifically specified in the embodiments are all obtained commercially. The operation without special mention of temperature is carried out at room temperature. The operating methods and conditions not specifically specified can adopt the known or conventional means and conditions in this field. The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0157] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a structural chromogenic cellulose fabric, characterized in that: The steps include: A sodium carboxymethyl cellulose aqueous solution with a mass concentration of 0.1% to 0.5% is prepared, the nano-microsphere solution is mixed with the sodium carboxymethyl cellulose aqueous solution, the pH value is adjusted to 6.0 to 7.0, and the structure color slurry is obtained after being stirred evenly; The prepared structural color slurry is applied to the surface of the cellulose fabric and placed in a constant temperature and humidity environment for 1-6 hours to obtain the structural color cellulose fabric; the sodium carboxymethyl cellulose is used to connect the nano-microspheres and the cellulose fabric, and the nano-microspheres are polystyrene-divinylbenzene polymer microspheres coated with polydopamine; The preparation method further comprises the following curing step: curing the structural chromogenic cellulose fabric at 120-150° C. for 30-120 min to obtain a cured structural chromogenic cellulose fabric; The nano-microsphere solution is prepared by dispersing polydopamine-coated polystyrene-divinylbenzene polymer microspheres in water to obtain a nano-microsphere solution with a mass concentration of 20-50wt%.

2. The preparation method according to claim 1, characterized in that: The volume ratio of the nanosphere solution to the sodium carboxymethyl cellulose aqueous solution in the structural color paste is 2:1 to 1:

2.

3. The preparation method according to claim 1, characterized in that: The volume ratio of styrene to divinylbenzene in the polystyrene-divinylbenzene polymer microspheres during polymerization is 9:1-8:

2.

4. The preparation method according to claim 1, characterized in that: The average particle size of the polystyrene-divinylbenzene polymer microspheres is 180-350nm; the monodispersity index of the polystyrene-divinylbenzene polymer microspheres is less than 0.

1.

5. The preparation method according to claim 4, characterized in that: The polydopamine-coated polystyrene-divinylbenzene polymer microspheres are prepared by the following method: dopamine hydrochloride and an iron salt oxidation catalyst are added to an aqueous dispersion of polystyrene-divinylbenzene polymer microspheres, the mixture is evenly mixed, the temperature is raised to 30-60° C., and the reaction is stirred for 5-120 minutes to promote dopamine oxidation polymerization to wrap the polystyrene-divinylbenzene polymer microspheres, thereby obtaining the polydopamine-coated polystyrene-divinylbenzene polymer microspheres.

6. The preparation method according to claim 5, characterized in that: When preparing the polydopamine-coated polystyrene-divinylbenzene polymer microspheres, the product obtained by the reaction is washed with deionized water, dispersed under ultrasound and then centrifuged to obtain the polydopamine-coated polystyrene-divinylbenzene polymer microspheres.

7. The preparation method according to claim 5, characterized in that: When dopamine hydrochloride is added, the concentration of dopamine hydrochloride in the system is 0.1-1 mg / mL.

8. The preparation method according to claim 5, characterized in that: When the iron salt oxidation catalyst is added, the concentration of the iron salt oxidation catalyst in the system is 0.1-1 mg / mL.

9. The preparation method according to claim 5, characterized in that: The aqueous dispersion of polystyrene-divinylbenzene polymer microspheres is prepared by the following method: dispersing polystyrene-divinylbenzene polymer microspheres in water and treating them under ultrasound for 5-30 minutes to obtain an aqueous dispersion of polystyrene-divinylbenzene polymer microspheres with a concentration of 1-10 mg / mL.

10. The preparation method according to claim 5 or 9, characterized in that: The iron salt oxidation catalyst is one or more selected from ferric chloride, ferric sulfate, ferric nitrate, and ferric acetate.

Citation Information

Patent Citations

  • Method for increasing stability of photonic crystal structures on textiles

    CN106351023A

  • Preparation method of structural-color fabric

    CN106894245A